What's in a song? Combining analytical and arts-based analysis for songs created by songwriters with neurodisabilities. Issue 3 (27th May 2017) - Viega, Michael; Baker, Felicity A.
ABSTRACT: There are a number of methods for analyzing songs that are created and used in music therapy, which vary according to investigators' theoretical orientation and the intent of the inquiry. This article looks to understand the benefits and constraints of combining analytic approaches of song analysis with an experiential, arts-based investigation. The authors analyzed a series of songs created by a songwriter with a neurodisability, one author conducting a deductive analysis and the other engaging in experiential approaches from within an arts-based research (ABR) methodology. Results indicate that both analyses revealed similar information regarding the songwriter's self-concept, attributes, and rehabilitative needs in the context of her recovery from a neurodisability. However, deductive analysis provided an objective perspective that attempted to generalize themes, which might be useful to inform diagnostic information involving self-concept after a neurodisability. Conversely, but complimentary, an experiential approach allowed for more ambiguous and complex content to be explored, illuminating psychological and developmental processes that might not have been otherwise revealed in analytical analysis. The benefits and limitations of integrating analytic and experiential approaches to analyzing songs created by songwriters in music therapy are discussed to provide researchers and clinicians rationales for investigating songs from varying theoretical perspectives.